The gelation mechanism and network structure of polysaccharide food gels as studied from macroscopic, microscopic to molecular levels — A review of methodologies - Weifeng Li; Xi Yang; Haopeng Wang; Yisu Yang; Xingfeng Shao; Marwa E. Atya; Shingo Matsukawa (Food Hydrocolloids, 2027)

Integration of advanced spectroscopic and optical imaging techniques with chemometrics for detecting chilling injury in agricultural products - Haizhen Ding; Rui Ding; Yonghuan Yun; Yingying Wei; Weijie Lan; Kang Tu; Xingfeng Shao; Leiqing Pan (Postharvest Biology and Technology, 2026)

Exogenous hydrogen sulfide enhances peach resistance to Monilinia fructicola through pathogenesis-related proteins, phenylpropanoid metabolism, and reactive oxygen species homeostasis - Gang Chen; Yi Chen; Yingying Wei; Shu Jiang; Jianfen Ye; Jiahui Chen; Feng Xu; Christian Chervin; Xingfeng Shao (Postharvest Biology and Technology, 2026)

Hydrogen sulfide reduces postharvest water loss in peach fruit by enhancing cuticular wax accumulation and inhibiting pectin degradation - Kaining Jin; Yi Chen; Manlin Wang; Yingying Wei; Shu Jiang; Jianfen Ye; Jiahui Chen; Feng Xu; Xingfeng Shao (Plant Science, 2026)

Role of 2-phenylethanol in regulating population density and biocontrol efficacy of Scheffersomyces spartinae W9 via quorum sensing - Siyi Wu; Xiurong Zou; Yingying Wei; Jiamei Li; Yi Chen; Shu Jiang; Jianfen Ye; Feng Xu; Xingfeng Shao (International Journal of Food Microbiology, 2026)

Preharvest spraying of alginate oligosaccharide improved the postharvest storability of peach fruit by inhibiting sucrose decomposition and cell wall degradation - Qianting Wu; Yingying Wei; Yi Chen; Shu Jiang; Jianfen Ye; Feng Xu; Xingfeng Shao (Postharvest Biology and Technology, 2026)

Onion aqueous extract enhances the nutritional quality of fresh-cut potatoes and its subsequent processing flavor - Jiayue Huang; Shu Jiang; Fengru Zhang; Yingying Wei; Yi Chen; Jianfen Ye; Feng Xu; Phebe Ding; Xingfeng Shao (Postharvest Biology and Technology, 2026)

Contribution of various pectin fractions and internal condition to gel formation in wooly peach fruit during cold storage - Xiangwen Fang; Jianfen Ye; Cheng Li; Xi Yang; Jing Li; Yingying Wei; Shu Jiang; Yi Chen; Feng Xu; Xingfeng Shao (Food Chemistry, 2026)

Fucoidan enhanced brown rot resistance in postharvest peach fruit by regulating lignin biosynthesis - Yongyan Wu; Yi Chen; Yingying Wei; Feng Xu; Phebe Ding; Elsherbiny A. Elsherbiny; Fangming Wu; Xingfeng Shao (Food Bioscience, 2026)

Gelation of gellan in sucrose solutions as studied by rheology, particle tracking, micro-DSC, and 1H NMR measurements - Junhao Qiu; Weifeng Li; Haopeng Wang; Xingfeng Shao; Yi Chen; Yingying Wei; Jianfen Ye; Xi Yang (Food Hydrocolloids, 2026)

PpMYC2 positively regulates chilling tolerance of peach fruit by suppressing sucrose degradation - Qian Li; Yingying Wei; Yi Chen; Shu Jiang; Jianfen Ye; Fangming Wu; Feng Xu; Xingfeng Shao (Postharvest Biology and Technology, 2026)

A WRKY IIc transcription factor, FaWRKY47 enhances postharvest resistance to Botrytis cinerea in strawberry via activation of jasmonate biosynthesis and antioxidant defenses - Xin Ling; Yi Chen; Yingying Wei; Shu Jiang; Jianfen Ye; Jiahui Chen; Feng Xu; Fangming Wu; Xingfeng Shao (Postharvest Biology and Technology, 2026)

BoLrgB promotes programmed cell death of postharvest broccoli through regulating antioxidant pathways under oxidative stress - Jiacheng Li; Jiajun Lou; Jiahui Chen; Shifeng Cao; Yi Chen; Yingying Wei; Xingfeng Shao; Feng Xu (Postharvest Biology and Technology, 2026)

The PpERF4/PpERF061-PpCBF1 molecular cascade regulates sucrose metabolism to influence the cold resistance of peach fruit - Xingxing Wang; Yi Chen; Yingying Wei; Shu Jiang; Jianfen Ye; Jiahui Chen; Feng Xu; Elsherbiny A. Elsherbiny; Xingfeng Shao (Postharvest Biology and Technology, 2025)

PpWRKY4 regulates chilling injury in peach fruit by activating PpVIN2 and accelerating sucrose metabolism - Yongyan Wu; Shiyun Zhang; Yi Chen; Yingying Wei; Feng Xu; Phebe Ding; Xingfeng Shao (Postharvest Biology and Technology, 2025)

Characterization and formation process analysis of peach fruit woolliness under low-temperature storage - Jiajia Xu; Jianfen Ye; Cheng Li; Yuqing Guo; Weixiang Jiang; Xi Yang; Yingying Wei; Shu Jiang; Yi Chen; Xingfeng Shao (Food Chemistry, 2025)

Age differences in spontaneous cerebrovascular reactivity at rest - Allison C. Engstrom; Shubir Dutt; John Paul M. Alitin; Arunima Kapoor; Trevor Lohman; Isabel J. Sible; Anisa J. Marshall; Fatemah Shenasa; Jillian L. Joyce; Aimée Gaubert; Farrah Ferrer; Amy Nguyen; et al. (GeroScience, 2025)
Deficits in cerebral blood flow (CBF) and cerebrovascular reactivity (CVR) may indicate vulnerability to vascular dysfunction and cognitive impairment. Prior findings on age-related change in CVR are mixed, and no studies to date have investigated age group differences in spontaneous CVR (sCVR) at rest. The present study compared whole brain and regional sCVR at rest between 24 healthy younger adults (ages 18–34) and 163 cognitively unimpaired older adults (ages 55–87). Relative to younger adults, older adults had deficits in both whole brain and regional sCVR at rest. Among the regions examined, medial temporal lobe areas showed the largest age differences in sCVR at rest. Age differences in sCVR and CBF variability were larger than age differences in mean CBF. Results show age-related deficits in sCVR are present even in cognitively unimpaired older adults, suggesting sCVR may be indicative of cerebrovascular aging. Further research should investigate sCVR as a means for early detection of age-related vascular dysfunction that may predate irreversible vascular brain injury.

Contrasting effects of habitat fragmentation on community stability of breeding and wintering birds in urban green spaces - Xiangxu Liu; Di Zeng; Yuhao Zhao; Shao-peng Li; Shaopeng Wang; Bicheng Li; Xiao Yuan; Shunqi Bo; Xingfeng Si (Urban Forestry & Urban Greening, 2025)

Island Biogeography and Life‐History Traits Stabilize Island Bird Communities - Yuhao Zhao; Di Zeng; Thomas J. Matthews; Dylan Craven; Morgan W. Tingley; Shaopeng Wang; Shao‐peng Li; Ping Ding; Xingfeng Si (Global Change Biology, 2025)
Islands are model systems for testing and developing ecological theories. Despite extensive research on island biodiversity, the importance of the biogeographic context for biodiversity–stability relationships is poorly understood. We addressed this knowledge gap by integrating the Equilibrium Theory of Island Biogeography (ETIB) with a functional perspective to explore island biodiversity–stability relationships. We conducted annual breeding bird surveys across 36 land‐bridge islands in eastern China over 13 years. Using this long‐term dataset, we quantified avian temporal community stability (and its components of population stability and population asynchrony) and tested how island biogeographic factors (i.e., island area, isolation, colonization rates, and extinction rates) and biodiversity facets (i.e., species richness, average population size, and life‐history traits) interact to influence stability. We found larger islands supported higher species richness due to colonization–extinction dynamics and habitat heterogeneity, which in turn promote both population stability and asynchrony. In addition, larger islands harbored larger and individually more stable populations over time. In contrast, island isolation had a weak net effect on stability, as its positive and negative influences through different pathways balanced each other out. Furthermore, species with ‘fast’ life‐history traits, characterized by shorter generation times, contributed more to community stability. These findings clarify multiple pathways through which biogeographic factors shape avian community dynamics on islands. Our study thus illustrates how island biotas maintain community stability and provides insights for preserving biodiversity and ecosystem functioning in fragmented or island‐like landscapes facing rapid biodiversity loss in an era of global change.

The function of BoVDAC3 from broccoli in oxidative stress response and programmed cell death in BY-2 cells - Yuan Qian; Jiahui Chen; Shifeng Cao; Min Luo; Wenhui Jiao; Yi Chen; Yingying Wei; Xingfeng Shao; Feng Xu (Postharvest Biology and Technology, 2025)

Factor analysis of multimodal MRI, biofluid, and vascular biomarkers reveals latent constructs of brain health - Ella Rowsthorn; Ming Ann Sim; William T. O’Brien; Stuart J. McDonald; Katherine Franks; Benjamin Sinclair; Trevor T.-J. Chong; Stephanie Yiallourou; Marina Cavuoto; Lucy Vivash; Terence J. O’Brien; Xingfeng Shao; et al. (GeroScience, 2025)
Individual imaging and fluid biomarkers provide insights into specific components of brain health, but integrated multimodal approaches are necessary to capture the complex, interrelated biological systems that contribute to brain homeostasis and neurodegenerative disease. Using data from the Brain and Cognitive Health (BACH) cohort study ( N = 127; mean age = 67 years, 68% women), we performed an exploratory factor analysis to identify latent constructs of brain health. We included multimodal neurovascular imaging markers, brain atrophy metrics, plasma Alzheimer’s disease (AD) biomarkers, and cardiovascular risk factors. Five constructs emerged: “Brain & Vascular Health” (greater hippocampal volume, basal ganglia enlarged perivascular spaces (ePVS), cerebral blood flow, and HDL cholesterol; lower ventricle volume and BMI), “Structural Integrity” (greater cortical thickness, fractional anisotropy, and basal ganglia ePVS), “White Matter (WM) Fluid Dysregulation” (greater WM ePVS and Free Water), “AD Biomarkers” (higher phosphorylated tau [pTau]181 and pTau217; lower amyloid-beta 42/40 ratio), and “Neuronal Injury” (higher glial fibrillary acidic protein and neurofilament light chain). All constructs were associated with age (β = - 0.70–0.39, p ≤ 0.014), except for WM Fluid Dysregulation ( p > 0.05). Brain and Vascular Health and Structural Integrity (partial r = 0.305, p < 0.001) and AD biomarkers and neuronal injury (partial r = 0.248, p = 0.005) were positively correlated. Only Brain and Vascular Health was associated with global cognition (β = 0.27, SE = 0.13, p = 0.043). These findings provide a data-driven framework for examining distinct constructs underlying vascular health, fluid regulation, and neurodegenerative pathology. We demonstrate the utility of using multiple biomarkers to probe these biological systems, paving the way for future research to explore how these systems change across diverse neurodegenerative conditions. Graphical abstract

Jasmonic acid signaling pathway is involved in agaro-oligosaccharides-induced disease resistance of peach fruit through PpMYC2-activated transcription of PpPGIP1 - Qian Li; Yingying Wei; Shu Jiang; Jianfen Ye; Yi Chen; Feng Xu; Yongjiang Lou; Phebe Ding; Xingfeng Shao (Postharvest Biology and Technology, 2025)

Broccoli stem extract enhances browning inhibition in fresh-cut peach fruit by inhibiting polyphenol oxidase activity and improving antioxidant capacity - Fengru Zhang; Shu Jiang; Shuang Jia; Boya Gui; Yingying Wei; Yi Chen; Jianfen Ye; Feng Xu; Phebe Ding; Xingfeng Shao (Postharvest Biology and Technology, 2025)

Sucrose induces BoVDAC2 expression to preserve mitochondrial function and mitigate programmed cell death in broccoli - Min Luo; Jiahui Chen; Shifeng Cao; Xintong Guo; Yuan Qian; Wenhui Jiao; Hangjun Chen; Yi Chen; Yingying Wei; Xingfeng Shao; Feng Xu (Postharvest Biology and Technology, 2025)

Cinnamon essential oil causes cell membrane rupture and oxidative damage of Rhizopus stolonifer to control soft rot of peaches - Zichang Zhao; Mingxia Yu; Yingying Wei; Feng Xu; Shu Jiang; Yi Chen; Phebe Ding; Xingfeng Shao (Food Control, 2025)

Synergistic effects of plasma S100B and MRI measures of cerebrovascular disease on cognition in older adults - Colleen Pappas; Christopher E. Bauer; Valentinos Zachariou; T. J. Libecap; Beatriz Rodolpho; Tiffany L. Sudduth; Peter T. Nelson; Gregory A. Jicha; Anika MS Hartz; Xingfeng Shao; Danny J. J. Wang; Brian T. Gold (GeroScience, 2025)
There is growing interest in studying vascular contributions to cognitive impairment and dementia (VCID) and developing biomarkers to identify at-risk individuals. A combination of biofluid and neuroimaging markers may better profile early stage VCID than individual measures. Here, we tested this possibility focusing on plasma levels of S100 calcium-binding protein B (S100B), which has been linked with blood–brain-barrier (BBB) integrity, and neuroimaging measures assessing BBB function (water exchange rate across the BBB (k w )) and cerebral small vessel disease (white matter hyperintensities (WMHs)). A total of 74 older adults without dementia had plasma samples collected and underwent cognitive assessment. A subsample had neuroimaging data including diffusion prepared pseudo-continuous arterial spin labeling (DP-pCASL) for assessment of BBB k w and T2-weighted fluid-attenuated inversion recovery (FLAIR) for quantification of WMHs. Results indicated that higher plasma S100B levels were associated with poorer episodic memory performance ( β = − .031, SE = .008, p < .001). Moreover, significant interactions were observed between plasma S100B levels and parietal lobe BBB k w (interaction β = .095, SE = .042, p = .028) and between plasma S100B levels and deep WMH volume (interaction β = − .025, SE = .009, p = .007) for episodic memory. Individuals with the poorest memory performance showed both high plasma S100B and either low BBB k w in the parietal lobe or increased deep WMH burden. Taken together, our results provide support for the combined use of biofluid and neuroimaging markers in the study of VCID.

Gene co-expression network analysis of the transcriptome identifies cold-resistant hub genes related to carbohydrate metabolism in peach fruit - Xianzhu Deng; Yingying Wei; Yi Chen; Phebe Ding; Feng Xu; Xingfeng Shao (Postharvest Biology and Technology, 2025)

Recent advances in the application of tea tree oil in the storage of fruit and vegetables - Xianzhu Deng; Yingying Wei; Shu Jiang; Jianfen Ye; Yi Chen; Feng Xu; Jiahui Chen; Xingfeng Shao (Postharvest Biology and Technology, 2025)

Hydrogen sulfide attenuates chilling injury in loquat fruit by alleviating oxidative stress and maintaining cell membrane integrity - Xinyan Shen; Yu Liu; Yuan Zeng; Yaqin Zhao; Yinqiu Bao; Xingfeng Shao; Zhengguo Wu; Yonghua Zheng; Peng Jin (Food Chemistry, 2025)

Agaro-oligosaccharides enhanced the Monilinia fructicola resistance of peach fruit by regulating antioxidative and phenylpropanoid metabolism - Qian Li; Yingying Wei; Yi Chen; Shu Jiang; Jianfen Ye; Feng Xu; Yongjiang Lou; Phebe Ding; Meriem Ouaziz; Xingfeng Shao (Postharvest Biology and Technology, 2024)

γ-aminobutyric acid (GABA) inhibits programmed cell death in fresh-cut pumpkin by maintaining mitochondria structural and functional integrity - Jiahui Chen; Jingyi Liang; Shifeng Cao; Hongfei Wang; Yingying Wei; Yi Chen; Xingfeng Shao; Feng Xu (Postharvest Biology and Technology, 2024)

Activation mechanism of fatty acids on membrane-bound polyphenol oxidase in peach fruit: Conformational change analysis and molecular docking simulation - Qiufang Zhu; Shu Jiang; Yingying Wei; Yi Chen; Jianfen Ye; Phebe Ding; Xingfeng Shao (Food Bioscience, 2024)

BomMDH1 regulates malate-mediated oxidative stress in tobacco BY-2 suspension cells - Haohui Chen; Shifeng Cao; Jiahui Chen; Hongfei Wang; Yingying Wei; Yi Chen; Xingfeng Shao; Feng Xu (Journal of Plant Physiology, 2024)

Transcriptome analysis reveals the mechanism of antifungal peptide epinecidin-1 against Botrytis cinerea by mitochondrial dysfunction and oxidative stress - Li Fan; Yingying Wei; Yi Chen; Meriem Ouaziz; Shu Jiang; Feng Xu; Hongfei Wang; Xingfeng Shao (Pesticide Biochemistry and Physiology, 2024)

Transcriptome analysis reveals that trehalose alleviates chilling injury of peach fruit by regulating ROS signaling pathway and enhancing antioxidant capacity - Xingxing Wang; Yingying Wei; Shu Jiang; Jianfen Ye; Yi Chen; Feng Xu; Xingfeng Shao (Food Research International, 2024)

Influence of flavonoids from Sedum aizoon L. on mitochondrial function of Rhizopus nigricans in strawberry - Qingqing Ge; Shiyi Zhao; Xingfeng Shao; Yingying Wei; Jiahui Chen; Hongfei Wang; Feng Xu (World Journal of Microbiology and Biotechnology, 2024)

Hydrogen sulfide mediated methyl jasmonate -induced cold resistance in peach fruit - Miaomiao Yu; Yi Chen; Qiufang Zhu; Xuping Wu; Shu Jiang; Yingying Wei; Jianfen Ye; Feng Xu; Xingfeng Shao (Postharvest Biology and Technology, 2024)

Corrigendum to “PpZAT10 negatively regulates peach cold resistance predominantly mediated by inhibiting VIN activity” [Postharvest Biol. Technol. 190 (2022) 111952] - Yi Chen; Jiachang Sun; Yingying Wei; Kefeng Cao; Shu Jiang; Xingfeng Shao (Postharvest Biology and Technology, 2024)

Exogenous melatonin delays programmed cell death in broccoli via maintenance of ROS homeostasis and reduction of mitochondrial dysfunction - Zhiwei Jiang; Jiajun Lou; Shifeng Cao; Jiahui Chen; Hongfei Wang; Yingying Wei; Yi Chen; Xingfeng Shao; Feng Xu (Postharvest Biology and Technology, 2024)

Transcriptomic analysis reveals the resistance mechanism of flavonoids from Sedum aizoon L. to Rhizopus nigricans in postharvest strawberry fruit - Qingqing Ge; Shiyi Zhao; Xingfeng Shao; Yingying Wei; Jiahui Chen; Hongfei Wang; Feng Xu (Postharvest Biology and Technology, 2024)

Combined application of alginate oligosaccharide and marine yeast Sporidiobolus pararoseus to control brown rot of peach fruit - Jiamei Li; Yingying Wei; Yi Chen; Jianfen Ye; Shu Jiang; Feng Xu; Xingfeng Shao (Postharvest Biology and Technology, 2024)

Generalist and topologically central avian frugivores promote plant invasion unequally across land‐bridge islands - Chen Zhu; Bo Dalsgaard; Wande Li; Fernando Gonçalves; Maximilian G. R. Vollstädt; Peng Ren; Xue Zhang; Junjie Shao; Ping Ding; Xingfeng Si (Ecology, 2024)
Seed dispersal by frugivorous birds facilitates plant invasions, but it is poorly known how invasive plants integrate into native communities in fragmented landscapes. We surveyed plant–frugivore interactions, including an invasive plant ( Phytolacca americana ), on 22 artificial land‐bridge islands (fragmented forests) in the Thousand Island Lake, China. Focusing on frugivory interactions that may lead to seed dispersal, we built ecological networks of studied islands both at the local island (community) and at landscape (metacommunity) levels. On islands with P. americana , we found that P. americana impacted local avian frugivory networks more on islands with species‐poor plant communities and on isolated islands. Moreover, as P. americana interacted mainly with local core birds (generalists), this indicates reduced seed dispersal of native plants on invaded islands. At the landscape level, P. americana had established strong interactions with generalist birds that largely maintain seed‐dispersal functions across islands, as revealed by their topologically central roles both in the regional plant–bird trophic network and in the spatial metanetwork. This indicates that generalist frugivorous birds may have facilitated the dispersal of P. americana across islands, making P. americana well integrated into the plant–frugivore mutualistic metacommunity. Taken together, our study demonstrates that the impact of plant invasion is context‐dependent and that generalist native frugivores with high dispersal potential may accelerate plant invasion in fragmented landscapes. These findings highlight the importance of taking the functional roles of animal mutualists and habitat fragmentation into account when managing plant invasions and their impact on native communities.

A cyclodextrin metal-organic framework loaded with terpinen-4-ol and its application to control gray mold in strawberry - Lingling Yu; Xingxing Wang; Yingying Wei; Shu Jiang; Jianfen Ye; Yi Chen; Feng Xu; Hongfei Wang; Xingfeng Shao (Food Control, 2024)

1-Methylcyclopropene reduces postharvest water loss by modulating cuticle formation in tomato fruit - Xuping Wu; Yi Chen; Jingjing Zhu; Ni Zhang; Yingying Wei; Shu Jiang; Jianfen Ye; Xingfeng Shao (Postharvest Biology and Technology, 2023)

Regional differences in the link between water exchange rate across the blood–brain barrier and cognitive performance in normal aging - Valentinos Zachariou; Colleen Pappas; Christopher E. Bauer; Xingfeng Shao; Peiying Liu; Hanzhang Lu; Danny J. J. Wang; Brian T. Gold (GeroScience, 2023)
The blood–brain barrier (BBB) undergoes functional changes with aging which may contribute to cognitive decline. A novel, diffusion prepared arterial spin labeling-based MRI technique can measure the rate of water exchange across the BBB ( k w ) and may thus be sensitive to age-related alterations in water exchange at the BBB. However, studies investigating relationships between k w and cognition have reported different directions of association. Here, we begin to investigate the direction of associations between k w and cognition in different brain regions, and their possible underpinnings, by evaluating links between k w , cognitive performance, and MRI markers of cerebrovascular dysfunction and/or damage. Forty-seven healthy older adults (age range 61–84) underwent neuroimaging to obtain whole-brain measures of k w , cerebrovascular reactivity (CVR), and white matter hyperintensity (WMH) volumes. Additionally, participants completed uniform data set (Version 3) neuropsychological tests of executive function (EF) and episodic memory (MEM). Voxel-wise linear regressions were conducted to test associations between k w and cognitive performance, CVR, and WMH volumes. We found that k w in the frontoparietal brain regions was positively associated with cognitive performance but not with CVR or WMH volumes. Conversely, k w in the basal ganglia was negatively associated with cognitive performance and CVR and positively associated with regional, periventricular WMH volume. These regionally dependent associations may relate to different physiological underpinnings in the relationships between k w and cognition in neocortical versus subcortical brain regions in older adults.

Mannose delays senescence in broccoli florets via maintaining mitochondrial morphological structure and function - Xintong Guo; Shifeng Cao; Hongfei Wang; Yingying Wei; Yi Chen; Shu Jiang; Xingfeng Shao; Feng Xu (Postharvest Biology and Technology, 2023)

ERF transcription factor PpRAP2.12 activates PpVIN2 expression in peach fruit and reduces tolerance to cold stress - Kefeng Cao; Shiyun Zhang; Yi Chen; Jianfen Ye; Yingying Wei; Shu Jiang; Xingfeng Shao (Postharvest Biology and Technology, 2023)

Melatonin treatment delays postharvest senescence of broccoli with regulation of carotenoid metabolism - Jiajun Lou; Chenghao Wu; Hongfei Wang; Shifeng Cao; Yingying Wei; Yi Chen; Shu Jiang; Xingfeng Shao; Feng Xu (Food Chemistry, 2023)

Stability and release of peach polyphenols encapsulated by Pickering high internal phase emulsions in vitro and in vivo - Yu Song; Leyi Zhou; Decai Zhang; Yingying Wei; Shu Jiang; Yi Chen; Jianfen Ye; Xingfeng Shao (Food Hydrocolloids, 2023)

Soluble dietary fiber from Prunus persica dregs alleviates gut microbiota dysfunction through lead excretion - Mei Yao; Xintong Guo; Xingfeng Shao; Yingying Wei; Xin Zhang; Hongfei Wang; Feng Xu (Food and Chemical Toxicology, 2023)

Influences of flavonoids from Sedum aizoon L. on the cell membrane of Botrytis cinerea - Kaiyue Wang; Qingqing Ge; Xingfeng Shao; Yingying Wei; Xin Zhang; Feng Xu; Hongfei Wang (Food Bioscience, 2023)

Epinecidin-1, a marine antifungal peptide, inhibits Botrytis cinerea and delays gray mold in postharvest peaches - Li Fan; Yingying Wei; Yi Chen; Shu Jiang; Feng Xu; Chundan Zhang; Hongfei Wang; Xingfeng Shao (Food Chemistry, 2023)

A transcriptome analysis of the antibacterial mechanism of flavonoids from Sedum aizoon L. against Shewanella putrefaciens - Jing Wang; Zongyu Chi; Ke Zhao; Hongfei Wang; Xin Zhang; Feng Xu; Xingfeng Shao; Yingying Wei (World Journal of Microbiology and Biotechnology, 2020)

Transcriptome analysis of Penicillium italicum in response to the flavonoids from Sedum aizoon L. - Jie Luo; Feng Xu; Xin Zhang; Xingfeng Shao; Yingying Wei; Hongfei Wang (World Journal of Microbiology and Biotechnology, 2020)

Antifungal mechanism of sodium dehydroacetate against Geotrichum citri-aurantii - Xu Tang; Qiuli Ouyang; Guoxing Jing; Xingfeng Shao; Nengguo Tao (World Journal of Microbiology and Biotechnology, 2018)

Effects of Postharvest Hot Air Treatment on Gene Expression Associated with Ascorbic Acid Metabolism in Peach Fruit - Ke Wang; Xingfeng Shao; Yifu Gong; Feng Xu; Hongfei Wang (Plant Molecular Biology Reporter, 2014)